DESIGNING A GEOMETRY OF LOWWALL SLOPE IN COAL MINING USING THE LIMIT-EQUILIBRIUM METHOD AT THE WORKING AREA OF PT. PETROSEA TBK, TARAKAN BASIN, NORTH KALIMANTAN, INDONESIA - Fauzan, Aldo; Muslim, Dicky; Endyana, Cipta; Wandani, Diki; Fiverno, David Feby; Putra, Rieza Rachmat (Faculty of Geological Engineering, Universitas Padjadjaran, 2024)
Mining, which involves extracting minerals and utilizing natural resources, requires careful planning to ensure feasibility and safety. A critical aspect of open pit mine design is slope stability, influenced by geological characteristics, slope topography, and groundwater conditions. Slope stability analysis, using methods such as the Limit Equilibrium Method (LEM), which has been popular for decades for its convenience, evaluates the potential for slope failure and provides geometric slope design recommendations to reduce risk, improve operational efficiency, and ensure environmental sustainability. The research was conducted at PT Petrosea Tbk, with the mine site in Sebakis Village, Sebuku Subdistrict, Nunukan Regency, North Kalimantan, PT X region. The research object is a lowwall slope that requires stability analysis to prevent landslides. The slope safety criteria are based on the Minister of Energy and Mineral Resources Decree No. 1827 K/30/MEM/2018 guidelines, specifically 1.1. To perform the analysis, laboratory test data is required, including rock physical property tests and rock shear strength tests to obtain material property values. This data was then analysed using Rocscience Slide2 software by comparing three methods: Bishop, Janbu, and Morgenstern-Price. The analysis was conducted based on the actual conditions of each slope cut geometry. If the obtained safety factor does not meet the criteria of the Minister of Energy and Mineral Resources Decree No. 1827 K/30/MEM/2018, then designing a geometry of lowwall slope is required. The geometric slope design used on the lowwall slope includes creating benches to flatten the slope level, and installing drain holes to decrease the ground water level.